Sulfamethazine Transport in Agroforestry and Cropland Soils. Issue 2 (22nd March 2013) - Chu, Bei; Anderson, Stephen H.; Goyne, Keith W.; Lin, Chung-Ho; Lerch, Robert N.
Abstract : Knowledge of veterinary antibiotic (VA) transport and persistence is critical to understanding environmental risks associated with these potential contaminants. To understand mobility of sulfamethazine (SMZ) and sorption processes involved during SMZ transport in soil, batch sorption experiments were conducted and column leaching experiments were performed with repacked soil columns containing silt loam soils collected from cropland (Crop) and an agroforestry (AGF) vegetative buffer system. Bromide (Br − ) was applied as a nonreactive tracer to characterize the flow of water. Radio‐labeled ( 14 C) SMZ with or without 150 mg L −1 of manure‐derived dissolved organic carbon (DOC), was added as a pulse and leaching of the compounds was monitored for 21 d. Sulfamethazine concentration in the leachate was monitored using a liquid scintillation counter and high performance liquid chromatography analysis confirmed absence of SMZ degradation product in the leachate. Breakthrough curves of SMZ and Br − were constructed for each column. Bromide breakthrough curves were fitted with a convection/dispersion based transport equilibrium model with no sorption, whereas SMZ breakthrough curves were fitted with multisite sorption chemical nonequilibrium transport models with linear or Freundlich sorption components. Results indicated that the three‐site model containing two reversible sites (one instantaneous and one kinetic) and one irreversible site coupled with the Freundlich sorption component (3S2R‐Freu‐irrev model) best described SMZ transport through the columns with model efficiencies of 0.998, 0.994, and 0.991 for AGF, AGF + DOC and Crop soils, respectively. No difference or small difference between fitted sorption parameters, such as the linear sorption coefficient ( K d ), Freundlich sorption coefficient ( K f ), and Freundlich nonlinearity parameter ( N ), and those obtained from equilibrium sorption experiments was observed. Data from equilibrium sorption experiments and column transport experiments suggested that the AGF soil was able to retain a larger quantity of SMZ than the Crop soil, and DOC had little effect on SMZ sorption or leaching. Greater SMZ retention by the AGF soil compared to the Crop soil suggests that vegetative buffers may be a viable means to mitigate VA loss from agroecosystems.